EP330/#475 Immune-based biomarker accurately predicts response to imiquimod immunotherapy in cervical high-grade squamous intraepithelial lesions. (4th December 2022) - Esch, Edith Van; Abdulrahman, Ziena; Hendriks, Natasja; Kruse, Arnold Jan; Somarakis, Antonios; Sande, Anna; Beekhuizen, Heleen Van; Piek, Jurgen; Miranda, Noel De; Kooreman, Loes; Slangen, Brigitte; Burg, Sjoerd Van Der; et al.
Abstract : Objectives: Topical imiquimod is a non-invasive alternative to a Large Loop Excision of the Transformation Zone (LLETZ) in the treatment of cervical high-grade squamous lesions (cHSIL), and is effective in approximately 60% of primary cHSIL. Prediction of therapy responses upon imiquimod could increase therapy efficacy and aid in patient selection and counselling. Methods: Two multispectral seven-color immunofluorescence panels for T cell and myeloid cell composition were used to study the immune composition in relation to imiquimod response in 35 cHSIL patients on biopsies before and 10 weeks on imiquimod treatment. Based on these results a simplified immunohistochemical detection protocol was developed. Results: The immune microenvironment ( figure 1 ) of complete responders (CR) prior to imiquimod is characterized by a strong and coordinated infiltration by T helper cells (activated PD1 + /type 1 Tbet + ), M1-like macrophages (CD68 + CD163 - ) and dendritic cells (CD11c + ). The lesions of non-responders (NR) displayed a high infiltration of CD3 + FOXP3 + regulatory T cells. Based on the pre-existing immune composition differences a quantitative simplified one color immunohistochemical biomarker approach was developed which can be automatically and unbiasedly quantified and has an excellent predictive capacity for complete response to therapy (ROC AUC 0.95, p<0.0001; figure 2 ). Conclusions: A pre-existing coordinated local immune response was associated with the capacity of cHSIL patients to respond to imiquimod. This allowed to develop an easy to apply immunohistochemical biomarker approach to select cHSIL patients with a high likelihood to experience a complete response to imiquimod immunotherapy.